Effect of the Supports’ Positions on the Vibration Characteristics of a Flexible Rotor Shafting - Miaomiao Li; Zhuo Li; Liangliang Ma; Rupeng Zhu; Xizhi Ma (Shock and Vibration)
In this study, we evaluated the effect of changing supports’ position on the vibration characteristics of a three-support flexible rotor shafting. This dependency was first analyzed using a finite element simulation and then backed up with experimental investigations. By computing a simplified rotor shafting model, we found that the first-order bending vibration in a forward whirl mode is the most relevant deforming mode. Hence, the effect of the supports’ positions on this vibration was intensively investigated using simulations and verified experimentally with a house-made shafting rotor system. The results demonstrated that the interaction between different supports can influence the overall vibration deformation and that the position of the support closer to the rotor has the greatest influence.